Biofabrication: Development of Endothelial Cell Networks in 3D Tissues by Combination of Melt Electrospinning Writing with Cell‐Accumulation Technology (Small 2/2018). Issue 2 (11th January 2018) - Bertlein, Sarah; Hikimoto, Daichi; Hochleitner, Gernot; Hümmer, Julia; Jungst, Tomasz; Matsusaki, Michiya; Akashi, Mitsuru; Groll, Jürgen
Abstract : In article1701521, Mitsuru Akashi, Jürgen Groll, and co‐workers use a cell‐accumulation technique for the controlled formation of tubular structures in cellular constructs. The image is a confocal laser scanning microscopy image showing HUVECs attached to polycaprolactone scaffolds with 100 μm pores produced by melt electrowriting after 1 day of incubation.